The Effect of Entrepreneurial Orientation, Customer Orientation, and Knowledge Sharing on Innovation Capability and Business Performance (Study on Tourism-Based MSMEs in Banyuwangi Regency) - Ahmad Fauzen; Muhammad Iqbal; Yusri Abdillah (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Tourism is a potential sector to be developed in order to stimulate Indonesia's economic growth. Along with the depletion of natural resource reserves which have become the foundation of extractive industries, the government must begin to develop other renewable sectors to increase economic growth. In this study, explained the influence of entrepreneur orientation, customer orientation and knowledge sharing on innovation capability and business performance. This type of research is explanatory research, using a questionnaire primary data collection tool distributed to tourism-based MSME owners in Banyuwangi Regency. The sample in this study was a saturated sample, by making all tourism-based MSME owners in Banyuwangi Regency a sample of 94 respondents. The data analysis technique using smart PLS 20.0 was chosen to analyze the influence of variables in this study. The results showed that entrepreneur orientation, and customer orientation had a positive and significant effect on innovation capability and business performance, knowledge sharing had a significant positive effect on innovation capability, but knowledge sharing was not significant for business performance.